Perbedaan Penguasaan Statistika Dan Kemampuan Menulis Karya Ilmiah Mahasiswa PGSD Ditinjau Dari Jenis Kelamin Dan Asal Daerah - Bulkani Bulkani (Institute For Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
This study aims to examine whether there is a difference in statistical mastery and the ability to write scientific papers on UM Palangkaraya PGSD students, both multivariate and univariate if viewed from the gender and origin of the student area. The research method used was descriptive-comparative, with a sample of 94 people. The research time is at the beginning of the even semester 2014/2015. Data analysis techniques use MANOVA. From the results of data analysis, it was concluded that (1). There were differences in statistical mastery and the ability to write scientific papers when viewed from gender, with an F value of 3.993 which was significant at the level = 5% (p = 0.022 <0.05). (2). There are differences in statistical mastery and the ability to write scientific papers if viewed from the origin of the student area, with an F value = 7.307 which is significant at the level = 5% (p = 0.000 <0.05). (3). The ability to write female student scientific work is better than male students with a significant F = 5.211 at the level of = 5%. (4). There is a difference in the mastery of statistics on students if viewed from the origin of the region with a value of F = 4.575 which is significant at the level = 5%. Based on the average sample, the best statistical mastery is for students from urban areas, followed by students from urban areas and then by students from rural areas. (5). There are differences in the ability to write scientific papers if viewed from the origin of the student area, with a value of F = 11.151 which is significant at the level = 5% Based on the average sample, the best ability to write scientific work is for students from urban areas, followed by students from urban areas and then by students from rural areas.